Fire in the plaça : Catalan festival politics after Franco - Noyes, Dorothy (EBL-Schweitzer, 2003)
"This impressive contribution to the anthropology of Europe is the first full-length study in English of the Patum, a Corpus Christi fire festival unique to the town of Berga, in the foothills of the Catalan Pyrenees (Spain) It also marks the emergence of an important scholar ... Highly recommended."--Choice